2004
DOI: 10.1901/jaba.2004.37-97
|View full text |Cite
|
Sign up to set email alerts
|

Extended Diaper Wearing: Effects on Continence in and Out of the Diaper

Abstract: Diaper use is widespread and possibly even increasing across diverse populations in the United States, ranging from infants to very old adults. We found no reports of an experimental analysis of the effect of wearing diapers on the frequency of urinary accidents and the attainment of continence skills (e.g., urinating in the toilet). In this study, we used a withdrawal design to evaluate the effect of wearing diapers on daily urinary accidents and successful voids for an adult who had been diagnosed with menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 5 publications
3
23
0
Order By: Relevance
“…Behavior analysts have evaluated some of these recommended training procedures, often with individuals with intellectual or developmental disabilities and within multicomponent training packages (for a recent review of the training procedures used with children with developmental disabilities, see Kroeger & Sorensen‐Burnworth, ). For example, Tarbox, Williams, and Friman () found decreases in accidents and increases in appropriate eliminations when diapers were removed for an adult with an intellectual disability. Simon and Thompson () extended Tarbox et al by demonstrating improvements in toileting performance when typically developing children wore underwear instead of diapers.…”
mentioning
confidence: 99%
“…Behavior analysts have evaluated some of these recommended training procedures, often with individuals with intellectual or developmental disabilities and within multicomponent training packages (for a recent review of the training procedures used with children with developmental disabilities, see Kroeger & Sorensen‐Burnworth, ). For example, Tarbox, Williams, and Friman () found decreases in accidents and increases in appropriate eliminations when diapers were removed for an adult with an intellectual disability. Simon and Thompson () extended Tarbox et al by demonstrating improvements in toileting performance when typically developing children wore underwear instead of diapers.…”
mentioning
confidence: 99%
“…A Japanese study showed that 56% of the subjects used diapers or similar devices, and diapers were used in 24% of still continent persons mainly for protective purposes (8). Wearing pads however may increase the rate of accidents and decrease the rate of successful voids (52). Even in studies of younger women a high contribution to the overall cost of UI is attributable to pad usage (10).…”
Section: Discussionmentioning
confidence: 99%
“…For women who have not had their incontinence evaluated and only use absorbent products, they face a likely future that the UI will not improve. Also if women do not select and use the appropriate absorbent products for their UI, then urinary tract infections, IAD, delays in help seeking for UI, increased rate of falls, increased severity of SUI, and decreased rate of successful voids could occur …”
Section: Discussionmentioning
confidence: 99%